Determination of the optimum temperatures and mass ratios of steam injected into turbocharged internal combustion engines - Gonca, Guven; Sahin, Bahri; Ust, Yasin; Parlak, Adnan (AMER INST PHYSICS, 2013)
Water injection method into the internal combustion engines is commonly used to improve performance and emissions. However, condensed water causes to deteriorate the lubrication oil, in-cylinder corrosion is carried out and also wear rate of moving parts of engine increases. In order to prevent this bad effect of condensed water, steam injection is proposed. Electronically controlled steam injected method has been used for naturally aspirated engines and successful results have been obtained in terms of performance and NOx emissions. However, supercharged engine systems are used in practical life. In this study, steam injection method is developed for turbocharged systems. The optimum temperatures and mass ratios are determined based on thermo dynamical analyses. (C) 2013 American Institute of Physics. [http://dx.doi.org/10.1063/1.4798313]
Keywords: TRANSIENT LOAD CONDITIONS; DIESEL-ENGINE; NOX EMISSIONS; PERFORMANCE; SYSTEM; FUEL; CYLINDER; BIODIESEL; EMULSIONS; BALANCES; Science & Technology - Other Topics; Energy & Fuels